Business Incubator Organizational Communication Patterns In Efforts to Empower MSMEs in Lampung Province - Azizah, Tazkiyah; Luqman, Yanuar (KOMUNIKA, 2023)
Siger Innovation Hub (Sigerhub) is a business incubator that impacts efforts to develop the potential of MSMEs in Lampung Province. Sigerhub has various coaching programs such as talent hub, incubation, funding & market access, which are presented as "Siger Business Sprint" events. Considering the critical role of Business Incubators in creating enthusiasm for new businesses, evaluation of business Incubators is necessary so that empowerment of MSMEs is more optimal. This event is inseparable from communication processes. This research systematically analyzes communication patterns and strategies in events to optimize the coordination system from planning to evaluating activities so that MSME empowerment efforts can run optimally. Using organizational communication theory and innovation diffusion theory, and the research method uses descriptive qualitative with a case study approach to obtain communication patterns and strategies. The results revealed that the communication pattern in the Siger Business Sprint event used a predominantly wheel structure. The communication strategies are based on media, instructional design, participation, and marketing. Researchers found that there were obstacles to using inappropriate communication patterns and strategies in several event implementation conditions, so the benefits couldn’t reach all community groups, especially those who didn’t have businesses. Using appropriate patterns and strategies can maximize efforts to develop MSMEs and foster a spirit of entrepreneurial motivation for all community groups.